Psychometric Properties of the Affective Dimension of the Generic Macro-Competence Assessment Scale: Analysis Using Rasch Model. - Morales-Rodríguez, Francisco Manuel; Martí-Vilar, Manuel; Narváez-Peláez, Manuel; Giménez Lozano, José Miguel; Martínez-Ramón, Juan Pedro; Caracuel, Alfonso (MDPI, 2021)
The study of the affective dimension of transversal competences is essential for the develop- ment of responsible behaviors and maintaining attitudes committed to sustainable development. The importance attributed to each of these factors can predict behavior implementation and awareness of values for sustainable development that reflect the acquisition and internalization of sustainability- related generic competences. This study aimed to determine the psychometric properties of the affective dimension of the Generic Macro-Competence Assessment (AGMA) scale by applying Rasch measurement model to a sample of Spanish university students, comprising 387 Spanish university students (74.9% women; mean age = 21.24; WD = 3.54; range: 17–34). Results demonstrated a lack of adjustment to the Rasch model due to item 1, and all items showed disordered response cate- gory thresholds. The remaining nine-item scale achieved all requirements of the model (χ2 = 61.46; p = 0.052), including unidimensionality. Thus, the scale’s psychometric properties indicate an easy- to-apply instrument for screening these factors for coping strategies in undergraduate and graduate Spanish students. The results can help in justifying the design of interdisciplinary intervention programs, in which affective factors are essential for sustainable development education.
Keywords: Afecto (Psicología); Estudiantes universitarios - Psicología; Psicometría; Generic competencies; Common good; Socio-affective factors; Sustainability education; University students